2015
DOI: 10.4185/rlcs-2015-1057en
|View full text |Cite
|
Sign up to set email alerts
|

Branded Entertainment: Entertainment content as marketing communication tool. A study of its current situation in Spain

Abstract: One of these tools is branded entertainment, a kind of hybrid message used by brands to produce entertainment content. Method: the main objective of this article is to provide a better understanding of branded entertainment, and to explore its current situation and the expectations about its future in the Spanish market. This is an exploratory study based on in-depth interviews applied to a group of experts on the creation and distribution of branded entertainment. Results and conclusions: people involved in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Entertainment plays the main role in this purpose through social media. According to De Aguilera-Moyano et al, (2015), brand entertainment created the highest potential instrument, which is an effective message for producing entertainment content.…”
Section: Literature Review Social Media Marketing Activitiesmentioning
confidence: 99%
“…Entertainment plays the main role in this purpose through social media. According to De Aguilera-Moyano et al, (2015), brand entertainment created the highest potential instrument, which is an effective message for producing entertainment content.…”
Section: Literature Review Social Media Marketing Activitiesmentioning
confidence: 99%
“…Balasubramanian (1994) defined hybrid messages as ‘as any paid attempt to influence an audience with a commercial goal, by using communications with non-commercial appearance’. The advantage of such messages is that consumers consume such content with more attention and responsiveness as they have chosen to engage with the content (de Aguilera Moyano et al, 2015). However, BC can be educational, entertaining and informational (de Aguilera Moyano et al, 2015), having a similar dimension of advertising value as suggested by Ducoffe (1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The advantage of such messages is that consumers consume such content with more attention and responsiveness as they have chosen to engage with the content (de Aguilera Moyano et al, 2015). However, BC can be educational, entertaining and informational (de Aguilera Moyano et al, 2015), having a similar dimension of advertising value as suggested by Ducoffe (1995). Ducoffe (1995) posited that consumers’ value advertising, which is perceived as credible messages (CR), entertaining (ENT) or informative (INF).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies mainly considered executional characteristics when examining the recall and recognition of placed brands. However, audience emotional experiences may have an impact on their cognitive perceptions and memory (de Aguilera-Moyano et al , 2015; Hudson and Hudson, 2006). The dimensional emotional theory (Lang, 1979) defines emotion in terms of arousal, valence and dominance, which has a significant impact on cognitive memory (Berger, 2012; Lang and Dhillon, 1995; Moorman et al , 2007).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…The existing literature suggests that audiences’ emotional experiences may have an impact on their cognitive perceptions and memory (de Aguilera-Moyano et al , 2015; Hudson and Hudson, 2006). Nevertheless, previous studies on product placement have mainly focused on the effects of executional characteristics on brand recall and recognition.…”
Section: Introductionmentioning
confidence: 99%